2008
DOI: 10.1002/dvg.20355
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inactivation of Hs6st1 in mice is associated with late postnatal mortality without major defects in organogenesis

Abstract: Summary: Heparan sulfate (HS) proteoglycans modulate the biological activity of a number of growth factors in development, homeostasis, and cancer. Specific modifications of HS chains by HS biosynthetic enzymes have been implicated in growth factor signaling in multiple aspects of organogenesis. Although the role of HS 6-O-sulfotransferases has been described in processes such as trachea formation in Drosophila and vasculogenesis in zebrafish, little is known about how HS 6-O-sulfotransferases (Hs6st1-3 in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Gengrinovitch et al (53) have suggested glypican-1 as a VEGF 165 -binding proteoglycan, but endothelial cells express other membrane proteoglycans as well (54). Studies are underway to identify the functional HSPG that interacts with VEGFR2 and VEGF 165 and whether the interaction with heparan sulfate depends on the arrangement of sulfate residues in the chain, e.g., by examining how hyperpermeability is affected in tissue-specific mutants altered in uronyl 2-O-sulfation (55) and glucosaminyl 6-O-sulfation (56). Systemic mutants altered in the expression of specific core proteins are also available, which should aid in the identification of the active proteoglycan(s) in this system (57).…”
Section: Discussionmentioning
confidence: 99%
“…Gengrinovitch et al (53) have suggested glypican-1 as a VEGF 165 -binding proteoglycan, but endothelial cells express other membrane proteoglycans as well (54). Studies are underway to identify the functional HSPG that interacts with VEGFR2 and VEGF 165 and whether the interaction with heparan sulfate depends on the arrangement of sulfate residues in the chain, e.g., by examining how hyperpermeability is affected in tissue-specific mutants altered in uronyl 2-O-sulfation (55) and glucosaminyl 6-O-sulfation (56). Systemic mutants altered in the expression of specific core proteins are also available, which should aid in the identification of the active proteoglycan(s) in this system (57).…”
Section: Discussionmentioning
confidence: 99%
“…flox and Hs2st flox mice have been previously described (20,27). Hs6st2 KO mice were obtained from Lexicon Genetics via Mutant Mouse Regional Resource Centers (MMRRC:011715-UCD).…”
Section: Mice-hs6st1mentioning
confidence: 99%
“…The biological and physiological importance of Hs6st-1 was determined by examining Hs6st-1 null (Hs6st-1−/−) mice. 35,36 Most of the Hs6st-1 −/− mice die between embryonic day 15.5 (E15.5) and the perinatal stage, and a low percentage of the mutant mice that survive are considerably smaller than their wild-type littermates (Table I). Some of the Hs6st-1 −/− mice exhibited developmental abnormalities, including a ~ 50 % reduction in the number of fetal microvessels in the labyrinthine zone of the developing placenta.…”
Section: Endothelial Heparan Sulfate In Developmental and Physiolomentioning
confidence: 99%